Hang Li Po - The Musical - Mohamad Ghouse Nasuruddin, (Wacana Seni Journal of Arts Discourse, 2004)
The Chinese Princess Hang Li Po has been featured as one of the important characters in the history of Melaka. According to history and legend, the Chinese Emperor sent his Princess as a gift in respect and admiration of the Sultan of Malacca. In addition, the Emperor hoped that this gift would establish cordial and friendly relations between China and Melaka and in recognition of Melaka as the administrative and commercial centre of the Old Malay World. In all probability, this gesture of the Chinese Emperor was not merely to honour the Sultan of Malacca but to secure Melaka as a trading outpost for the Chinese Empire. Thus, it would seem that the Emperor was willing to sacrifice his daughter for this purpose.